(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the lexical-semantic features of religious concepts presented in the dictionary “Ash-Shuzur az-Zahabiyya.” The study examines theonyms, religious terms, and lexical units related to worship and cosmological representations contained in the dictionary. Particular attention is given to the relationship between Arabic and Turkic lexical layers, the methods of interpretation, and the mechanisms of conceptual explanation. In addition, the historical and cultural foundations of religious notions are discussed on the basis of comparative materials. The results of the study contribute to revealing the process of the formation of religious terminology in medieval Turkic lexicography.